Fund and Fundamentals of Mathematics - Jayant Vishnu Narlikar (University Press, 2001)
This book introduces fundamental ideas in mathematics through intersting puzzles. Students, from age12 upwards, who are bored with routine classwork in maths will enjoy these puzzles which will sharpen will sharpen their logical reasoning. It is designed to arouse an interest in mathematics among readers among readers in the 12-18 age group.